Input for Instructed L2 Learners The Relevance of Relevance - Niżegorodcew, Anna (Multilingual Matters, 2007)
This book makes Relevance Theory (RT) relevant for L2 teachers and L2 teacher educators, in particular those working in foreign language teaching contexts. L2 classroom discourse data collected in seven research projects in the years 1984 – 2004 are reinterpreted in this book in the light of Relevance Theory - a theory of interpretation of the incoming messages. In this perspective the teachers’ input for instructed L2 learners facilitates shifts in the learners’ attention from meaning to form and vice versa. Such shifts of attention, according to Relevance Theory, change the level of expected optimal relevance of classroom communication, either focusing the students on form-oriented communication (accuracy), on meaning-oriented communication (fluency) or on meaning and form-oriented communication (fluency combined with accuracy). The latter is considered optimal for L2 learning/acquisition. Apart from the main focus on the relevance-theoretic interpretation of the teachers’ input, the book presents an overview of other theoretical approaches to the question of input for instructed L2 learners: the SLA approach, the communicative L2 teaching perspective, and the L2 classroom discourse approach
Description based on online resource; title from PDF title page (publisher's Web site, viewed 07. Dez 2018)
Keywords: classroom communication; classroom discourse; input in SLA.; L2 acquisition; L2 classroom discourse; L2 learners; L2 learning; L2 teachers; Relevance Theory; Second Language Acquisition; SLA.; Discourse analysis; Language and education; Language and languages -- Study and teaching; Second language acquisition